1982
DOI: 10.1111/j.1365-3059.1982.tb01275.x
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of Botrytis allii in field soil

Abstract: Neck rot (Botrytis allii) affected bulbs of onions for 2 successive years when these were grown either in the field in soil from which an infected crop had been cleared 6 months previously or when infected debris was incorporated into field soil 6 months before the first crop was sown. These sources did not continue to cause infection of onion crops grown on the contaminated areas in the four succeeding years. The white storage tissue of onion bulbs (healthy or infected) persisted for less than 6 months in uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…While symptoms develop during storage, infection takes place in the field [1]. Leaf tips are the primary infection court for B. aclada , from which the fungus starts to grow towards the onion neck [4,5] with primary inoculum being either seed‐borne [4,6] or soil‐borne [7]. Secondary spore production from necrotic leaf tips is epidemiologically important [4].…”
Section: Introductionmentioning
confidence: 99%
“…While symptoms develop during storage, infection takes place in the field [1]. Leaf tips are the primary infection court for B. aclada , from which the fungus starts to grow towards the onion neck [4,5] with primary inoculum being either seed‐borne [4,6] or soil‐borne [7]. Secondary spore production from necrotic leaf tips is epidemiologically important [4].…”
Section: Introductionmentioning
confidence: 99%
“…of inoculum in the surrounding area which could explain why the infection was detected earlier on onion plants during both sampling years. Other studies also confirmed that the conidia produced during the previous season can infect plants at the seedling stage (Maude and Presly 1977;Maude et al 1982;du Toit et al 2004), resulting in asymptomatic plants, which can develop symptoms of neck rot during storage (Maude 1990). Despite the seasonal variations in the temperature, relative humidity, and amount of precipitation that the Portage La Prairie area received during 2019 and 2020 (Figs.…”
Section: Discussionmentioning
confidence: 77%
“…Although the open wound resulting from the removal of foliage at harvest is an important site for bulb infection, many plants are infected early in the growing season without displaying visible disease symptoms (Maude, 1990). Conidia produced during the season can infect plants at the seedling stage (du Toit, et al, 2004;Maude et al, 1982;Maude and Presly, 1977), resulting in asymptomatic plants, which can develop symptoms of neck rot during storage (Maude, 1990). The ability to quantify the level of inoculum in bulbs at different sampling times either during growth or during storage could yield insight into the growth patterns or virulence of the pathogen.…”
Section: Discussionmentioning
confidence: 99%